Two new species of tribe Schistopterini (Diptera: Tephritidae: Tephritinae) with an updated key to species from the Oriental region - Hatwar, Nikhil Khemrajji; David, Karamankodu Jacob; Raghuraman, Mahadevan; Srinivasa, Narayana (Zootaxa, 2026)
Two new species of Schistopterini, Rhabdochaeta octomaculata Nikhil & David, sp. nov. and Rhochmopterum nongshillong Nikhil & David, sp. nov. are described, illustrated from India and keys to all species of these genera from the Oriental Region is provided.